2016
DOI: 10.1021/acs.nanolett.6b02727
|View full text |Cite
|
Sign up to set email alerts
|

Surface Sensing of Quantum Dots by Electron Spins

Abstract: The nanoscale design of quantum dots (QDs) requires advanced analytical techniques. However, those that are commonly used do not have sufficient sensitivity or spatial resolution. Here, we use magnetic resonance techniques combined with paramagnetic Mn impurities in PbS QDs for sensitive probing of the QD surface and environment. In particular, we reveal inequivalent proton spin relaxations of the capping ligands and solvent molecules, strengths and anisotropies of the Mn nuclear spin interactions, and Mn nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In our NMR studies, we observed significant shortening of the longitudinal relaxation time, T 1 , for protons in the capping ligands of Au NCs compared to that for protons in the ligand only. We note that the biggest difference is observed for the protons in the immediate proximity of the NC core (T 1 decreases from 1.61 to 0.64 s), as was shown previously for paramagnetic quantum dots [26] (see also supplementary information, S1). The observation of magnetism in AuNCs is of potential interest for their application in magnetic resonance imaging.…”
Section: Synthesis Of Folic Acid Functionalized Gold Nanoclusters Forsupporting
confidence: 82%
“…In our NMR studies, we observed significant shortening of the longitudinal relaxation time, T 1 , for protons in the capping ligands of Au NCs compared to that for protons in the ligand only. We note that the biggest difference is observed for the protons in the immediate proximity of the NC core (T 1 decreases from 1.61 to 0.64 s), as was shown previously for paramagnetic quantum dots [26] (see also supplementary information, S1). The observation of magnetism in AuNCs is of potential interest for their application in magnetic resonance imaging.…”
Section: Synthesis Of Folic Acid Functionalized Gold Nanoclusters Forsupporting
confidence: 82%
“…However, the separation between the peaks in the SQ (≈43 MHz) and DQ (≈84 MHz) doublets are larger than the expected values, 2ν I and 4ν I , respectively, revealing the contribution of second order hyperfine interactions trueright2νI=left2gNμNB/h+A2ν0[]S()S+1ms2left0.16emA3ν02[]S()S+1ms2O()A3For B = 1213 mT, A ≡ A iso = 267 MHz, ν 0 = 34 GHz, S = 5/2, and m s = 1/2, we find that 2ν I ≈ 43 MHz and 4ν I ≈ 86 MHz, in agreement with the experimental data. Finally, the peak at Δν ≈ 51 MHz is assigned to hydrogen‐atoms on the QD capping ligands weakly coupled to Mn spins …”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of the Materials and Samples Preparation : The Mn‐doped PbS QDs were synthesized in aqueous solution with an Mn weight content of 0.05%, which corresponds to a nominal average number of Mn ions per QD of 0.5. The surface of the QDs was passivated with thiolglycerol (TGL) molecules enabling the realization of nanostructures that are stable and optically active . The core of the QDs has the cubic rocksalt crystal structure of PbS and an average diameter d = 4.5 ± 1.2 nm (Figure a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the broadening of the NMR lines and the non-linear decrease of T 1 and T 2 with increasing Mn-content indicate much stronger effects at low Mn content (Mn o 1%), thus suggesting the preferential location of Mn close to the periphery of the nanocrystal. 31 Self-purification mechanisms 4 can lead to impurity out-diffusion resulting in greater impurity content in the proximity of the QD surface compared to the centre. 32 The greater Mn-dependent reduction of T 1 and T 2 times at low Mn compared to higher Mn content indicates a saturation of the concentration of Mn-ions close to the QD surface.…”
mentioning
confidence: 99%